D-Dimer Plasma Levels in Each Trimester of Diabetic Pregnant Women, A Case Control Study - Kanar Sadraddin Shamsaddin; Shahla Kareem Alalaf (Advanced Medical Journal)
Background and objectives: Pregnancy increases D-dimer levels, making it a non-specific test for venous thromboembolism. This study compared D-dimer levels by trimester in healthy and diabetic pregnant women.